Bioethics Yearbook
XI, 434 p.
Keywords: As noted in Volume 1, the Yearbook series alternates between a biennial volume tracing recent theological discussions on topics in bioethics and a biennial volume tracing recent regional discussions in bioethics. Volume 2 provides for the first time a comprehensive single-volume summary of recent international and regional developments on specific topics in bioethics. To give uniformity to the discussions all authors were asked to report on the following topics: new reproductive technologies, abortion, maternal-fetal conflicts, case of severely disabled newborns, consent of treatment and experimentation, confidentiality, equitable access to health care, ethical concerns raised by cost-containment measures, decisions to withhold or withdraw life-sustaining treatment, active euthanasia, the definition of death, organ donation and transplantation. The internationally respected contributors report on the following 16 areas: the United States, Canada, Latin America, the United Kingdom and Ireland, France, the Netherlands, Germany/Austria/Switzerland, Eastern Europe, Spain/Portugal/Italy/Scandinavia, India, Southeast Asia, China, Japan, Australia/New Zealand, Council of Europe/EEC. The commentators draw on three sets of resources: Statutes, legislative proposals, and regulatory changes that directly influence, or have implications for, areas of bioethical concern; Case law and court judgments that shape, either decisively or suggestively, recent legal interpretations of particular issues of areas in bioethics; Formal statements of governmentally appointed commissions, advisory bodies, and representative professional groups, as well as less formal statements and recommendations of other organisations. In addition to providing timely summaries of recent developments, the volume offers rich and useful bibliographical references to a wide array of documents, many of which would be difficult for readers to learn about, given the lack of centralized international collection of such documents. The Yearbook should be widely consulted by all bioethicists, public policy analysts, lawyers and theologians.